Shifting from Religious Populism to Authoritarian Populism: Two Decades of Identity Politics Dynamics in Indonesia - Arina Rohmatul Hidayah; Atwar Bajari; Dadang Rahmat Hidayat; Eni Maryani (Social Sciences, 2025)
This article aims to answer the question of whether identity-based movements are free from tendencies in political economy. By analyzing the actions and orientations of the militant Islamic group from the New Order to the Reform era, we show that social movements based on cultural identities are far from representing the demands of groups of recognition. Rather, these movements are leveraged as political tools for the executive group in determining dominant issues among the public to increase voter preferences and bring economic benefits to militant Islamic groups. This is insisted upon through a shift in political trends from religious populism to authoritarian populism. We argue that a possible solution could be prioritizing democratic values that lead to performance and integrity, not sectoral interests that can create fragmentation in society.